Optimization of The Combination of CMC-Na and Glycerin in Tobacco (Nicotiana tabacum L.) Hand Sanitizer Gel Using The Simplex Lattice Design - Andi Eko Wiyono; Iftitah Ariyanti Safitri; Andrew Setiawan Rusdianto; Miftahul Choiron; Ardiyan Dwi Masahid (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Tobacco leaves have active compounds such as phenols and alkaloids that can be used as antibacterial and antiseptic because they can damage the cell components of microorganisms. Tobacco leaf extract in hand sanitizer gel has been shown to have antibacterial activity against Staphylococcus aureus and Eschericia coli bacteria at a minimum concentration of 0.25%. Hand sanitizer is an antiseptic product that is used to clean hands and is preferred because it is practical, has a cooling and dries quickly when compared to hand soap. To make hand sanitizer products that are safe for the skin, various chemical compounds are used as building blocks, including CMC-Na and glycerin. CMC-Na acts as a gelling agent and glycerin has a role as a vehicle. This study aims to obtain the optimum formula for hand sanitizer gel preparations with variations in the concentration ratio of CMC-Na and glycerin using Simplex Lattice Design (SLD) and to determine the effect of variations in the concentration ratio of CMC-Na and glycerin on physical, chemical, and microbiological characteristics of the results of the optimum formula for hand sanitizer gel preparations. The research method used in this study is a type of laboratory experiment using Completely Randomized Design (CRD). The data obtained from the research results were processed using Analysis of Variance (ANOVA) with a 95% confidence level and continued with Duncan's Multiple Range Test at a significance level of 5%. The results showed that there were 3 optimum formulas for hand sanitizer gel of tobacco leaf extract based on the desirability value, 0.912 (Formula 1), 0.457 (Formula 4) and 0.653 (Formula 5). The variation of the concentration ratio of CMC-Na and glycerin in the optimum formula showed that CMC-Na had the most dominant influence on physical (homogeneity), chemical (total flavonoid) and microbiological (antibacterial and antiseptic) characteristics. Meanwhile, glycerin has the most dominant influence on product viscosity stability. The three optimum formulas have homogeneous gel characteristics.